2015
DOI: 10.1039/c5ra18246h
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the effect of monomers and green solvents on thermoresponsive copolymers: phase transition temperature and surface properties

Abstract: The thermoresponsive and surface properties of PNIPAM based copolymers were investigated in response to green solvents, ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In other words, the most dramatic temperature-triggered changes occur within the basic structural units which prevail in the solution at lower concentrations. Differentiation in aggregate types also explains the shift of kink location to higher temperatures: clusters formation promotes additional noncovalent bonds in the assemblies that consequently results in a stronger bonding and higher temperature of phase transition (this effect is similar to those observed in thermoresponsive copolymers when increasing the length of monomer chain 116 ).…”
Section: Energy and Fuelsmentioning
confidence: 58%
“…In other words, the most dramatic temperature-triggered changes occur within the basic structural units which prevail in the solution at lower concentrations. Differentiation in aggregate types also explains the shift of kink location to higher temperatures: clusters formation promotes additional noncovalent bonds in the assemblies that consequently results in a stronger bonding and higher temperature of phase transition (this effect is similar to those observed in thermoresponsive copolymers when increasing the length of monomer chain 116 ).…”
Section: Energy and Fuelsmentioning
confidence: 58%
“…It is reported that the folded conformation of BSA in water is attributed to the formation of a water shell around the BSA [ 49 ]. In the present study, the equal distribution of monomers, PEGMA and AA, cause PGA-1 to be more hydrophilic [ 39 ], and thereby this polymer can easily alter the hydration shell around the BSA. Moreover, the optimum amount of PEGMA in PGA-1 can increase the bulkiness of the backbone of polymer, and thereby, restricts the flexibility of the entire copolymer system and results in more hydrophilicity by hindering the formation of the intramolecular hydrogen bonds [ 39 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the equal distribution of monomers, PEGMA and AA, cause PGA-1 to be more hydrophilic [ 39 ], and thereby this polymer can easily alter the hydration shell around the BSA. Moreover, the optimum amount of PEGMA in PGA-1 can increase the bulkiness of the backbone of polymer, and thereby, restricts the flexibility of the entire copolymer system and results in more hydrophilicity by hindering the formation of the intramolecular hydrogen bonds [ 39 , 51 ]. Therefore, the behavior (flexible/stiff) of the polymer is the result of intermolecular hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations